2020
DOI: 10.3390/foods10010072
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Information Needs and Sensory Label Design for Fresh Fruit Packaging. An Exploratory Study in Spain

Abstract: In recent decades, packaged fruit has gained market ground over loose fruit, and fruit containers have become a source of information for consumers. This study approaches three objectives related to consumer information needs for decision making when purchasing fruit: (1) Determine if consumers’ choice of packaged fruit rather than loose fruit is motivated by their interest in the information provided on packaging; (2) identify information gaps on fruit packaging labels; (3) identify those sensory attributes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 67 publications
1
9
0
Order By: Relevance
“…In contrast, price was an important factor for about half of German peach buyers [ 55 ]. For UK respondents, the best before date was of relevance, as has been found previously in Spain [ 56 ]. Experience qualities such as taste were also important, as has also been noted in previous studies where it was linked to other experience attributes such as sweetness [ 19 ] contributing to a class of “experience attribute-oriented consumers”.…”
Section: Discussionsupporting
confidence: 69%
“…In contrast, price was an important factor for about half of German peach buyers [ 55 ]. For UK respondents, the best before date was of relevance, as has been found previously in Spain [ 56 ]. Experience qualities such as taste were also important, as has also been noted in previous studies where it was linked to other experience attributes such as sweetness [ 19 ] contributing to a class of “experience attribute-oriented consumers”.…”
Section: Discussionsupporting
confidence: 69%
“…Previous studies have shown that consumers may be very interested in receiving detailed product information for durable goods ( Burke, 2002 ). However, recent studies have indicated that when purchasing fruits, consumers may also express an interest in fruit origin information ( Fernández-Serrano et al, 2020 ). Thus, we included the climate, temperature, precipitation, and sunshine suitability of the origin besides the brand and price labels.…”
Section: Methodsmentioning
confidence: 99%
“…This result is consistent with the "IBM Food Sustainability Study 2020" report and the Altroconsumo survey, both of which agreeing that a lack of reliable food information holds Italian respondents back from eating greener products. In particular, according to Fernández-Serrano et al [69], the major information gap about sustainability issues perceived by food customers is related to "production method", "percentage of the price received by farmers", "postharvest treatments", "sensory properties", "harvest date" and "environmental information", and, therefore, the industry should make efforts to provide this information or make it clearer than it currently is. Considering the newly revoked findings, we argue that due to contrasting and scant information, consumers interested in sustainable products may not have the level of knowledge required to choose a brand and, therefore, they try different products since they are not directed towards a sustainable one, thus reducing their loyalty towards a specific brand.…”
Section: The Effect Of the Interest Of Consumers Towards Sustainable Productsmentioning
confidence: 99%